Identification of various T-2 toxin metabolites in chicken excreta and tissues. - Visconti, A (1985)
Gas chromatography-mass spectrometry was used to identify various T-2 toxin metabolites in chicken excreta and organs 18 h after intraperitoneal injection of the toxin. No trichothecenes were detected in the heart and kidneys, and only trace amounts were detected in the lungs. Most of the T-2 metabolites were found in the excreta, although considerable amounts were also found in the liver. In addition to the previously identified T-2 metabolites in chicken excreta (HT-2 toxin, 15 acetoxy T-2 tetraol, and T-2 tetraol), we found 3'-hydroxy HT-2 toxin (the major metabolite in excreta and organs), 3'-hydroxy T-2 toxin, 4-acetoxy T-2 tetraol, and trace amounts of 8-acetoxy T-2 tetraol, 3-acetoxy-3'hydroxy HT-2 toxin, and T-2 triol. Unmetabolized T-2 toxin and an unidentified isomer of T-2 tetraol monoacetate were also detected in the excreta. Most of the metabolites in the chicken are similar to those encountered in cultures of fungal species producing T-2 toxin. A comparison with T-2 toxin metabolism in the cow is also reported.